Genomic analyses of the scorpion mud turtle (Kinosternon scorpioides) (Linnaeus, 1766) in insular and continental Colombia: Evidence for multiple conservation and taxonomic units - Caballero, Susana; Martínez, Jose Gregorio; Morales-Betancourt, Monica A.; Bolaños, Nacor; Lasso, Carlos A. (Frontiers in Conservation Science, 2022)
The turtle genus Kinosternon is widespread with at least 25 species distributed from Mexico to northern Argentina. The taxonomy of this genus is controversial and requires a full revision using both morphological and molecular approaches. In this study, we did a genomic analysis on the species Kinosternon scorpioides distributed in insular and continental Colombia in order to define conservation units. Total DNA was extracted from 24 tissue samples and RADseq genotyping analysis was done. In addition, the intron R35 was amplified and sequenced for a subset of samples. A total of 35,507 SNPs combined with 1,047 bp of the intron were used for spatiotemporal colonization pattern reconstruction and phylogenetic analyses. In addition, SNPs were used for population structure inferences and allele frequency-based analyses. Reciprocal monophyly, significant differences in allele frequencies (Fst = 0.32 - 0.78), and evidence of reproductive isolation (no admixture/geneflow), indicate long-term divergence between groups (2-8 MYA), possibly due to geographical barriers. Four Evolutionarily Significant Units (ESUs) were defined within our samples. One ESU was represented by the insular subspecies K. scorpioides albogulare, found on San Andrés island, and three ESUs were defined for the subspecies K. s. scorpioides in continental Colombia: one trans-Andean, found in northwestern Colombia (Caribbean region) and two cis-Andean, found in eastern and southeastern Colombia in the Orinoco and Amazon regions, respectively. Colonization of this species occurred from an ancestral area on South of Central America region (~ 8.43 MYA), followed by an establishing of current populations on San Andrés Island and then, on the continent. First, on the Colombian Caribbean, next, on the Orinoco, and more recently, in the Amazon. We hypothesize that the emergence of the Panamá Isthmus, as well as the final uplift of the North Eastern Andes and Vaupes Arch, were key event leading to the differentiation of these ESUs. For management and conservation purposes, each of these ESUs should be considered as a separate management unit. A full revision of the taxonomy of the genus Kinosternon is warranted.